The impact of sleeping in an elevated upper body position during acclimatization to high altitude on acute mountain sickness and pulmonary artery systolic pressure - Maren Graß; Christian Apel; Daniela Bertsch; Carina Cerfontaine; Michael van der Giet; Simone van der Giet; Miriam Haunolder; Nina Hundt; Julia Jäger; Christian Kühn; Sonja Museol; Lisa Timmermann; et al. (University of Applied Sciences in Tarnow, Poland, 2023)
Background: The effect of sleeping positions during acclimatization to high altitude on Acute Mountain Sickness (AMS) and High Altitude Pulmonary Edema (HAPE) is unknown. We tested whether sleeping with the upper body raised by 5° reduces prevalence and severity of symptoms of AMS as well as of elevated pulmonary artery systolic pressure (PASP) values as a risk factor of HAPE. Methods: Randomly assigning trekking tourist volunteers n = 44 (25 m, 19 f; mean age 42.9 yr) sleeping at 4280 m or 5170 m to the experimental group (upper body elevated by 5°), or to the control group. After exclusion of other reasons for AMS-like symptoms those assumed to be related to AMS were rated by Lake Louise Score questionnaire in the evening and the following morning of the study. Transthoracic echocardiography was performed on both occasions to estimate PASP. Results: In the study group, symptoms of AMS were significantly reduced in younger subjects (p = 0.021), prevalence of AMS was reduced in women (p = 0.156), and PASP values were significantly reduced in older subjects and men (p = 0.032; p = 0.031 respectively). Conclusion: Results suggest that sleeping with the upper body in elevated position during a high altitude ascent may benefit those suffering from AMS or at risk of HAPE due to elevated PASP values.